Brain Cortex Morphology in Rats After Cold Exposures - Lomako, Viktoria; Shylo , Oleksandr; Pirozhenko, Liudmyla (Problems of Cryobiology and Cryomedicine, 2023)
Morphological changes of the brain cortex sensorimotor area in 6-month-old rats were studied after short-term intermittent and long-term continuous cold exposures (STICE and LTCCE, respectively). Under these conditions, perivascular and pericellular edema, small solitary foci of necrosis with gliosis phenomena, "porous" neuropil (signs under STICE at –12°С and formation during LTCCE), dystrophically changed neurons, neurons with nuclei at different stages of necrobiosis were noted in the brain tissue against the background of native cyto- and myeloarchitectonics, Some of the microvessels had signs of inflammation and thrombi. A moderate constriction (after STICE at –12°С) and a dilatation (after STICE at 10°С) of microvessels were observed. According to the fractal analysis, a decrease in the fractal dimension of the brain cortex sections was found under both STICE at –12°С and LTCCE. Probl Cryobiol Cryomed 2023; 33(3):193–200